Effect of Agraz (Vaccinium meridionale Swartz) on high-density lipoprotein function and inflammation in women with metabolic syndrome (2018)
ABSTRACT: Metabolic syndrome (MetS) is associated with low-grade inflammation and high-density lipoprotein (HDL) dysfunction. Polyphenol-rich foods may improve these alterations. Agraz is a fruit rich in polyphenols (mainly anthocyanins); however, there is limited information about its effects on human health. We evaluated the effects of agraz consumption as compared to placebo on HDL function and inflammation in women with MetS. Forty volunteers (25–60 years) were included in this double-blind crossover study. Women consumed agraz or placebo over 4 weeks; separated by a 4-week washout period. HDL function (apoliprotein-A1; paraoxonase 1 (PON1) activity; cholesterol efflux capacity), oxidative stress (myeloperoxidase (MPO), advanced oxidation protein products) and inflammatory markers (serum cytokines/chemokines and peripheral blood mononuclear cell nuclear factor-kB) were measured after each period. Compared to placebo, agraz consumption did not significantly change any of the biomarkers measured. Interestingly, only after agraz period there were significant positive correlations between PON1 activities and cholesterol efflux. Additionally, there were significant inverse correlations between changes in inflammatory markers and HDL function markers and positive correlations with oxidative markers. Although polyphenol-rich foods have been shown to be beneficial for certain conditions; polyphenol-rich agraz fruit consumption did not impact inflammation and HDL function in the current study of women with MetS.